Three new species of Euseius (Mesostigmata: Phytoseiidae) from Tamil Nadu, India, with redescription of Euseius ovalis and key to the Indian species - Biswas, Shubhadeep; Karmarkar, Krishna (Zootaxa, 2025)
Three new species of the genus Euseius Wainstein, 1962 (Mesostigmata: Phytoseiidae) namely, Euseius aridophilus Karmakar & Biswas sp. nov., Euseius madrasi Karmakar & Biswas sp. nov. and Euseius tamilicus Karmakar & Biswas sp. nov. are described and Euseius ovalis (Evans, 1953) is redescribed based on specimens collected from scrub forest regions of the state of Tamil Nadu, India. A key to the 50 Indian species of Euseius is provided. Euseius aridophilus Karmakar & Biswas sp. nov. is one of the most abundant phytoseiid mite species in the Indian states of Andhra Pradesh, Karnataka, Jharkhand, Odisha, Punjab, and Tamil Nadu.